SKILLS OF STUDENTS IN FORMALISTIC ANALYSIS OF DIFFERENT LITERATURE AND DEVELOPMENT OF INTERTEXTUAL MODULE - Yucada, Kimberly (International Journal of Arts, Sciences and Education, 2025)
This study focuses on students’ skills in formalistic analysis of literary works and the development of an intertextual module to ensure that activities and interventions are appropriate for students struggling with these skills. The research used a descriptive-developmental design. Their ability in formalistic analysis of stories was measured using an original 50-question test. Based on the test results, it was found that students struggled with the elements of style and authorial perspective, which led to the creation of the intertextual module. This module underwent a thorough review by Filipino language experts to assess its validity and acceptability. The output of the study can be used as an additional tool to enhance reading, comprehension, and analytical skills through formalistic methods.